Thyroid bud morphogenesis requires CDC42- and SHROOM3-dependent apical constriction - Loebel, David A. F. (Biol Open, 2016)
Early development of the gut endoderm and its subsequent remodeling for the formation of organ buds are accompanied by changes to epithelial cell shape and polarity. Members of the Rho-related family of small GTPases and their interacting proteins play multiple roles in regulating epithelial morphogenesis. In this study we examined the role of Cdc42 in foregut development and organ bud formation. Ablation of Cdc42 in post-gastrulation mouse embryos resulted in a loss of apical-basal cell polarity and columnar epithelial morphology in the ventral pharyngeal endoderm, in conjunction with a loss of apical localization of the known CDC42 effector protein PARD6B. Cell viability but not proliferation in the foregut endoderm was impaired. Outgrowth of the liver, lung and thyroid buds was severely curtailed in Cdc42-deficient embryos. In particular, the thyroid bud epithelium did not display the apical constriction that normally occurs concurrently with the outgrowth of the bud into the underlying mesenchyme. SHROOM3, a protein that interacts with Rho GTPases and promotes apical constriction, was strongly expressed in the thyroid bud and its sub-cellular localization was disrupted in Cdc42-deficient embryos. In Shroom3 gene trap mutant embryos, the thyroid bud epithelium showed no apical constriction, while the bud continued to grow and protruded into the foregut lumen. Our findings indicate that Cdc42 is required for epithelial polarity and organization in the endoderm and for apical constriction in the thyroid bud. It is possible that the function of CDC42 is partly mediated by SHROOM3.